Didymodon kunlunensis D.P.Zhao, S.Mamtimin & S.He (Pottiaceae), a new species from Xinjiang, China. (3rd April 2018) - Zhao, Dongping; Mamtimin, Sulayman; He, Si
Abstract : Didymodon kunlunensis D.P.Zhao, S.Mamtimin & S.He is described as a new species found in Xinjiang, China. The new species is characterised by a combination of the following characters: ovate leaves with laminal cells always smooth, red colour in KOH, recurved leaf margins from base to apex, a percurrent costa without dorsal and ventral stereid bands in cross section, a distinct stem central strand and the presence of gemmae in the leaf axils. Light microscope photographs of the significant characters are provided and its distinctions from closely related taxa are discussed. A key to Chinese Didymodon species with smooth laminal cell is provided.